2008
DOI: 10.1097/brs.0b013e31818c680a
|View full text |Cite
|
Sign up to set email alerts
|

CyberKnife Radiosurgery for Malignant Spinal Tumors

Abstract: Spinal radiosurgery with the CyberKnife technology is a nonivasive, safe, and effective treatment method for patients with 1 or 2 small spinal malignant tumors. The best benefit of the treatment can be expected in patients with good to excellent clinical condition and patients with severe tumor associated pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…Local tumour control of 240 treated metastases 15 months after SRS was 98% (95% CI 89-99%). As previously reported, the statistical model failed to identify factors predictive of local tumour control [23]. Median overall survival was 15.2 months after SRS.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Local tumour control of 240 treated metastases 15 months after SRS was 98% (95% CI 89-99%). As previously reported, the statistical model failed to identify factors predictive of local tumour control [23]. Median overall survival was 15.2 months after SRS.…”
Section: Resultsmentioning
confidence: 78%
“…Little is known about the control of spinal and cerebral lesions by systemic treatment alone, as the evaluation criteria used in phase III study protocols either exclude patients with cerebral lesions or disregard osseous lesions when evaluating remission. We have previously shown that single-session spinal and cerebral SRS is feasible, safe and effective, with the major benefits being short treatment times in an outpatient setting and rapid recovery from symptoms [8,9,21,23]. In our experience SRS not only stabilizes lesions, but also prevents further local problems in patients undergoing systemic therapy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Since the publication of that report, several other centers have evaluated the CyberKnife and other technologies for the treatment of spinal metastases with promising results. 5,[8][9][10][11][12]26,27 At the GUMC, Degen et al 5 have reported on the treatment of 51 patients with 72 spinal tumors. Lesions received a mean dose of 21.2 Gy over a mean of 3.6 fractions.…”
mentioning
confidence: 99%
“…No effort was made to specifically adjust dose homogeneity within the target because very different isodose levels (50% to 85%) are being used clinically 15 , 16 …”
Section: Methodsmentioning
confidence: 99%